2012
DOI: 10.1111/j.1468-2362.2013.12003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Banking Crises for Public Debt

Abstract: The aim of this paper is to assess the consequences of banking crises for public debt. Using an unbalanced panel of 154 countries from 1980 to 2006, the paper shows that banking crises are associated with a significant and long‐lasting increase in government debt. The effect is a function of the severity of the crisis. In particular, for severe crises, comparable to the most recent one in terms of output losses, banking crises are followed by a medium‐term increase of about 37 percentage points in the governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 50 publications
0
30
0
1
Order By: Relevance
“…The impact of the financial crisis on productivity growth can also be estimated using simple ordinary least squares (OLS) regression that incorporates crisis as a dummy independent variable and productivity growth as a dependent variable, which allows for the analysis of contemporaneous (static) associations between these variables. The advantage of using the method of impulse responses is that it allows for analyzing the dynamic impacts vis time lags (Furceri and Zdzienicka, ). This offers the opportunity to measure the impact of financial crisis on productivity growth several years after occurrence of the crisis.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of the financial crisis on productivity growth can also be estimated using simple ordinary least squares (OLS) regression that incorporates crisis as a dummy independent variable and productivity growth as a dependent variable, which allows for the analysis of contemporaneous (static) associations between these variables. The advantage of using the method of impulse responses is that it allows for analyzing the dynamic impacts vis time lags (Furceri and Zdzienicka, ). This offers the opportunity to measure the impact of financial crisis on productivity growth several years after occurrence of the crisis.…”
Section: Methodsmentioning
confidence: 99%
“…The recent experience with recessions has also shown that domestic fiscal policy cannot fully offset output shocks. 1 In addition, counter-cyclical expansionary measures may have significant and longlasting adverse effects on public debt sustainability (Reinhart and Rogoff 2010;Furceri and Zdzienicka 2013), which would, as shown by the recent events in the euro area, threaten the stability of the entire monetary union.…”
mentioning
confidence: 99%
“…There may be another factor that increases public debt and, at the same time, reduces credit: the occurrence of a banking crisis. There is evidence that banking crises are associated with a rise in government debt (Reinhart and Rogoff 2011;Furceri and Zdzienicka 2012). We accordingly consider the effect that previous bank crises might have on the dynamics of lending.…”
mentioning
confidence: 99%